PENGABDIAN MASYARAKAT BERBASIS POTENSI MENINGKATKAN KETRAMPILAN PERMAINAN FUTSAL TERHADAP SISWA EXTRAKULIKULER SMAN 3 BATU - I Gusti Komang Aldi; Chandra Bagus H; Chandra Wahyu P; Ahmad Junaidi (JPM PAMBUDI, 2023)
The purpose of this community service is to improve and introduce the game of futsal for futsal players at SMA Negeri 3 Batu, which is located in Sumbergondo Village, Bumiaji District, Batu City, East Java. The implementation method uses training that combines theory and practice for the participants. The results of this service basically the participants already have the basic technical skills of playing futsal very well 75% but 15% of them are still in the sufficient category and 10% are below the average futsal player. The conclusion from this dedication is that it is very important for the understanding of the players to be able to improve their ability to play futsal in order to achieve achievements in futsal.